Biodiesel Washing by the Prototype of a Biodiesel Washing Machine with Biochar - Surasak Fonghiransiri; Thatchapol Chungcharoen; Orasa Choolaaied; Siriwan Srisang; Naruebodee Srisang; Warunee Limmun (Journal of Advanced Research in Applied Mechanics, 2025)
Currently, the prevalent technique for biodiesel washing entails the utilization of water in the purification process. Nevertheless, this method incurs substantial biodiesel loss and gives rise to wastewater, posing potential environmental consequences. Hence, this study aimed to utilize biochar for removing impurities from biodiesel by using a prototype of a biodiesel washing machine with biochar. The effects of the propeller blade number, propeller blade angle, and mixing time on the capability to eliminate impurities in biodiesel were elucidated. The results indicated that the biodiesel washing machine can increase biodiesel yield by up to 2.49% (91.54%) compared to the water washing process (89.05%). The increased propeller blade number, angle, and mixing time can improve the acidity (24.50-64.04%) and water content removal (42.61-79.56%). Consequently, this led to a decrease in density (865.85-886.83 kg/m3) and viscosity (3.997-4.321 cSt). The conditions with the best biodiesel properties were five propeller blades, a propeller blade angle of 60 degrees, and a mixing time of 30 minutes. These conditions provided the 63.88% acid removal, 79.49% water content removal, viscosity of 878.92 kg/m3 and density of 4.208 cSt. Moreover, the methanol and glycerol contents were 0.02% wt. and 0.04% wt., respectively. These properties meet the ASTM 6751 and EN 14214 biodiesel standards.
Keywords: Biodiesel Production and Applications